Optimasi Optimasi Distribusi Air Irigasi untuk Memaksimalkan Keuntungan Pertanian Menggunakan Program Dinamis Deterministik di Daerah Irigasi Ameroro, Kabupaten Konawe - Yongki Adi Saputra; Lily Montarcih Limantara; Anggara Wiyono Wit Saputra (Postgraduate, University of Mataram, 2026)
Limited irrigation water availability constrains irrigation management and reduces agricultural profitability. This study aims to maximize agricultural profit by optimizing irrigation water distribution using a deterministic dynamic programming model in the Ameroro Irrigation Area, Konawe Regency, Indonesia. The model was structured with planting seasons as stages, irrigation water availability as the state variable, and water allocation as the decision variable. The objective function maximized total profit based on cultivated land area under a rice–rice–secondary crops cropping pattern across a total irrigated area of 2,100 ha. Model constraints included dependable discharge, seasonal water availability, crop water requirements, and land area limitations. In the existing condition, agricultural profit reached IDR 37.4 billion in planting season I, IDR 37.4 billion in planting season II, and IDR 8.6 billion in planting season III, totaling IDR 83.4 billion annually. After optimization, profits increased to IDR 42.03 billion, IDR 44.07 billion, and IDR 12.90 billion, respectively, resulting in a total annual profit of IDR 99.00 billion. The results indicate that deterministic dynamic programming improves water allocation efficiency and increases agricultural profit without additional water resources, supporting sustainable irrigation management.